In Reply. (10th February 2015) - Baratti, Dario; Kusamura, Shigeki; Maggi, Claudia; Braud, Filippo; Deraco, Marcello; Di Bartolomeo, Maria; Pietrantonio, Filippo
Abstract : The authors are currently conducting molecular and genetic research to identify new targets for therapeutic interventions and predictive biomarkers in pseudomyxoma peritonei. The final aim of these studies is to rationalize the choice of treatment, which remains an unmet clinical need.